CYTOTOXICITY AND ANTIOXIDANT ACTIVITY OF Boerhavia adscendens Willd. - A. KWAJI; R. ATIKO; I. M. UMAR (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Boerhavia adscendens (B. adscendens) is a medicinal plant with widespread use in folk medicine. The present study was aimed at evaluation of the cytotoxicity and antioxidant activity of the crude ethanol extract of B. adscendens. The cytotoxicity of the extract was determined using brine shrimp lethality assay while its antioxidant activity was assessed using ferric reducing antioxidant potential (FRAP). The study revealed that the B. adscendens extract has moderate cytotoxic effect against the brine shrimp larvae with LC50 of 100 μg/mL relative to K2Cr2O4 standard with LC50 of 0.01 μg/mL. The FRAP determination for B. adscendens extract yielded an IC50 of 34.56 μg/mL while the ascorbic acid standard had IC50 value of 31.25 μg/mL. These results demonstrate that the B. adscendens ethanol extract has moderate cytotoxicity and quite a significant antioxidant activity. Consequently, these findings may partly explain the usefulness of B. adscendens in traditional medicine.